Fanniidae and Muscidae (Insecta, Diptera) associated with burrows of the Altai Mountains Marmot (Marmota baibacina baibacina Kastschenko, 1899) in Siberia, with the description of new species - Sorokina, Vera S.; Pont, Adrian C. (Zootaxa, 2011)
One species of Fanniidae and eleven species of Muscidae including two new species have been found associated with the burrows of the Altai Marmot. New species are described (Hydrotaea barkalovi sp. nov. and Xestomyia atrox sp. nov.). Some taxonomic additions to the original male description of Fannia altaica Pont & Vikhrev, 2009 and the description of the female of this species are given. The male hypopygium, 5th sternite and abdomen in ventral view of Fannia altaica are figured, as are the legs and habitus of the two new species together with the male hypopygium and 5th sternite of Hydrotaea barkalovi sp. nov. A list of all the Muscidae and Fanniidae recorded as associated with burrows of the three Marmot species (Alpine Marmot, Altai Marmot, Long-Tailed Marmot) is given.